Challenges in Public-Private Partnership (PPP) projects in Malaysia - Diana Suwardi,; Suhana Saad, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The Public-Private Partnership (PPP) implementation approach in Malaysia aims to enhance the delivery of public sector infrastructure and services. However, the Auditor General's Report 2012 highlighted several deficiencies in PPP project management, including delays, poor quality, and inefficient resource use. This study seeks to identify the issues in the management of PPP projects in Malaysia that contribute to these ongoing problems and to propose improvements for enhancing PPP practices. Adopting a qualitative approach with an inductive single case study, the research involved semi-structured interviews with 14 participants conducted over one month in May 2024. The data were analyzed using NVivo Version 14 software through thematic analysis, which generated relevant codes, categories, themes, and domains. The findings reveal seven key strategic issues in PPP project management, such as accountability; incentives and assistance; values, norms, and prevalence; standards and procedures; good and moral governance; duties and roles; and laws and regulations. To improve PPP practices in Malaysia, it is essential for both the government and private sector key players in PPP project management to focus on enhancing capacity building and process optimization. This study provides valuable insights for future PPP project management in Malaysia and serves as a guide for strengthening PPP practices.